How is hydration assessed and managed in acute stroke? A qualitative study of healthcare staff's knowledge, attitudes and experiences. Issue 7 (18th April 2022) - Miller, Colette; Gibson, Josephine M. E.; Jones, Stephanie; Timoroska, Anne‐Marie; Maley, Alex; Romagnoli, Elisa; Chesworth, Brigit M.; Watkins, Caroline L.
Abstract: Aims and objectives: To explore healthcare staff's experiences of how dehydration is identified and managed in hospitalised patients after acute stroke, and facilitators and challenges to optimising hydration. Background: Optimal hydration post‐stroke reduces the risk of neurological deterioration and other complications. Patients are at risk of dehydration in acute stroke, particularly those with dysphagia. Design: A descriptive qualitative study reported following the COREQ guidelines. Methods: Semi‐structured interviews, utilising patient vignettes, were conducted in 2018 (Apr–Oct) with a purposive sample of 30 multidisciplinary staff members from two UK stroke units. Interviews were digitally recorded and transcribed verbatim. Content analysis identified common themes which were mapped to the Theoretical Domains Framework and the Behaviour Change Wheel. Results: The themes were mapped to twelve of the fourteen domains in the Theoretical Domains Framework. Participants believed that inadequate hydration management had potentially serious consequences, and described complex knowledge, skills and cognitive elements to effective hydration care. Participants felt that maintaining hydration was a multidisciplinary responsibility requiring good communication. Although the performance of initial dysphagia screening was reinforced by external audit, other areas of post‐stroke hydration management were not; notably, there was no established method of assessing hydration. Barriers to maintaining good hydration included lack of staff, out‐of‐hours working patterns, low priority given to hydration, patients' comorbidities and complex post‐stroke disabilities such as dysphagia, aphasia, inattention and hemiparesis. Conclusion: Findings highlighted the importance of assessing and maintaining hydration but identified barriers to, and variation in, clinical practice. To provide optimal care, barriers to the prevention and treatment of dehydration after stroke must be further understood and addressed. Relevance to clinical practice: Multidisciplinary teamwork is important in hydration care after stroke, but clarity is required about the specific contributions of each team member. Without this, hydration care becomes 'everybody's and nobody's job'.